Growth Rates of Arabica Coffee (Coffea arabica L) in the Pre-Nursery Stage with the Addition of a Combination of Chicken Feather Keratin and Blood Serum - Riko Pratama Siregar; Andi Setiawan; Kabul Warsito (Jurnal Multidisiplin Dehasen (MUDE), 2026)
This study aims to determine the growth rate of Arabica coffee (Coffea arabica L) in the pre-nursery stage with the addition of chicken feather keratin fertilizer and blood serum. This study used a factorial randomized block design (RAK) with two factors, namely. The first factor is chicken feather keratin fertilizer with 4 treatment levels (0.5, 10, 15 gr.), while the second factor is the addition of blood serum with 4 treatment levels (0.15, 30, 45 ml / L). This study is expected to provide information about the effect of chicken feather keratin and blood serum on the growth of Arabica coffee seedlings, and can be a reference.